German economy on a stable growth path - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Maximilian Podstawski; Thore Schlaak; Kristina van Deuverden (DIW Economic Bulletin, 2016)
Supported by dynamic domestic demand, the German economy is expected to grow by 1.7 percent this year. As consumption and investment in construction are likely to weaken in the coming year, is hardly contributing to growth 2017 should amount to roughly 1.4 percent. Foreign trade is contributing relatively little to growth. In both years of the forecast period, capacities will be at more or less normal levels of utilization; there are no signs of overheating. In the medium term, however, stronger investment in the capital stock is necessary to increase the growth potential of the German economy.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook